Spontaneous rupture of a congenital umbilical hernia in an infant: a rare complication (Bangladesh Journal of Medical Science, 2015)
Umbilical hernia is not uncommon in children. Most of these hernias close spontaneously as the children grows; they are often remarkably free from complications. Though in no way affecting the accepted principles of management of umbilical hernia, we feel that this case of spontaneous rupture is worth recording. To report a case of spontaneous rupture of a congenital umbilical hernia with evisceration of small intestines in a 45-day-old 3.5 kg female infant. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21574 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.100-102